PREVENTION STRATEGIES OF DESERTIFICATION (Web of Technology: Multidimensional Research Journal, 2024)
Desertification, a severe form of land degradation, poses significant threats to ecosystems and human livelihoods, particularly in arid and semi-arid regions. This review explores the primary causes of desertification, including climatic factors and anthropogenic activities, and examines effective prevention strategies. These strategies encompass sustainable land management practices, soil conservation techniques, afforestation, and water management. The article highlights case studies from various regions to illustrate successful interventions and discusses the role of policy and community involvement in combating desertification.